To solve the equation \( \frac{3}{4} (y + 8) = \frac{1}{2} (2y + 4) \) and determine if \( y = -20 \) is a solution, we can follow the steps of solving the equation while identifying the properties of equality used.
Step 1: Substitute \( y = -20 \)
We substitute \( y \) with \(-20\) into the equation:
\[ \frac{3}{4} (-20 + 8) = \frac{1}{2} (2(-20) + 4) \]
Step 2: Simplify both sides
- Left Side:
\[ -20 + 8 = -12 \]
Now substitute:
\[ \frac{3}{4} (-12) = -9 \]
- Right Side:
\[ 2(-20) + 4 = -40 + 4 = -36 \]
Now substitute:
\[ \frac{1}{2} (-36) = -18 \]
Step 3: Compare both sides
After simplification we have:
\[ -9 \neq -18 \]
Conclusion
Since \(-9\) does not equal \(-18\), \( y = -20 \) is not a solution for the equation \( \frac{3}{4} (y + 8) = \frac{1}{2} (2y + 4) \).
Properties of Equality Used
- Substitution Property: This allows us to replace \( y \) with \(-20\) in the equation.
- Addition Property of Equality: Used when simplifying expressions (e.g., combining like terms).
- Multiplication Property of Equality: Used to multiply the simplified values by constants (e.g., multiplying by \( \frac{3}{4} \) and \( \frac{1}{2} \)).
- Reflexive Property: If we were to analyze terms on each side independently, we could apply this property to establish equality through set values.
Thus, \( y = -20 \) does not satisfy the original equation.